The Influence of Foreign Investment and the Rupiah Exchange Rate on Indonesia's Economic Growth - Rinaldi, Muammar; Manurung, Johanes Adrian; Panjaitan, Rona A. P.; Sinurat, Evelyn; Fazira, Laila Era; Amelia , Ananda; Munthe , Justin Theo (Economic: Journal Economic and Business, 2024)
Ordinary Least Square (OLS) is one of the methods in multiple regression analysis to determine the effect of independent variables on dependent variables. To find out the effect of Foreign Direct Investment and Exchange Rate on Economic Growth, a quantitative analysis approach with Ordinary Least Square (OLS) model is needed. The objective of this research is to determine the effect of foreign investment and the rupiah exchange rate on economic growth in Indonesia. This research uses data on foreign investment in various sectors in the last 10 years, changes in the rupiah exchange rate between other countries' currency, and economic growth in Indonesia caused by various factors. And it is concluded that foreign investment has a positive but insignificant effect on the economic growth variable partially and rupiah exchange rate or rupiah exchange rate has unsignificant effect on the economic growth variable partially.